Evaluation of Nafion with Various Pt–C Concentrations in Membrane Electrode Assemblies for PEMFCs - K. Wuttikid (2018)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim Membrane electrode assemblies (MEAs) were fabricated directly onto the electrolyte membrane, using an ultrasonic spraying technique. Pt–C catalysts, with concentrations of 10%, 20% and 40% by weight, were used, and the Pt loading onto the MEAs was kept constant at 0.3 mg cm−2. Nafion contents were considered from 15% to 35 wt.%. The morphologies of the MEAs were evaluated by scanning electron microscopy (SEM), in which the agglomeration of Pt–C particles was imaged, and a secondary pore in the catalyst layers (CLs) was revealed. The cross-section images showed that the thickness of the CLs depended on the Pt–C concentration. The electrochemical surface area (ECSA) of those Pt–C concentrations and various compositions of Nafion contents were examined by cyclic voltammetry. Polarization curves were also measured and showed that the Nafion contents of 25 wt.%, 20 wt.%, and 15 wt.% gave the best performance for 10 wt.%, 20 wt.%, and 40 wt.% Pt–C catalysts, respectively. This indicates the Pt concentration is dependent on the Nafion content; the greater the weight of platinum in the catalysts, the less Nafion ionomer is required to optimize the electrochemical reaction. The data shows the same results regardless of the MEA fabrication techniques, operating conditions and Pt loadings.